Special Aspects of Leasing Activities and Its Meaning in Conditions of Enterprise Competitiveness - Kolpak, Eugeny P.; Gorynya, Ekaterina V.; Shaposhnikova, Aleksandra I.; Khasenova, Klara E.; Zemlyakova, Nataliya S. (International Review of Management and Marketing, 2016)
The relevance of this article is determined due to the fact that leasing as a form of entrepreneurial activities related to the transfer of property under a lease, it already is known abroad for several decades. At present, both in foreign and in domestic practice leasing basically ceased to be an element of innovation in the beginning of his understanding and implementation in economic activity. The importance of use evaluating of leasing schemes in the Russian practice is determined by the current state of the leasing sector of the Russian economy. Currently, the majority of Russian companies does not have sufficient amount of own funds for the purchase of modern production equipment. In this regard, there is a need to raise additional funds, the most common method which is to obtain bank loans. One of the alternative forms of financing the organization is leasing. In those cases where the lease as an investment method provides innovation, it takes on a new economic sense becomes an innovation. In this sense the economic category of leasing has not lost its relevance today as in the practical application, and its theoretical understanding. Russian economic theory and practice of management today pays insufficient attention to the study of these processes, the creation of adequate conditions for their implementation and regular development. Keywords: leasing, leasing administration, management, competitiveness JEL Classifications: G11, G31, L26